Plexiform Schwannoma in the Chest Wall: A Rare Case Report - Yakala Shreyas; Anchana Gulati; Deepika Sharma; Digvijay Singh Dattal (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Schwannomas are slow-growing tumors arising from the Schwann cells of the nerve sheath. The plexiform variant grows in a multinodular or plexiform pattern and may resemble either the conventional or cellular type. Clinically, these tumors are usually solitary, skin-colored nodules along the course of peripheral or cranial nerves, most commonly between 2 and 4 cm. They are typically found in the head and neck region or on the flexor surfaces of the extremities and may be associated with neurofibromatosis type 2, but not type 1. Most schwannomas show a histological biphasic pattern with compact Antoni A areas, sometimes with nuclear palisading and Verocay bodies, alternating with loosely arranged Antoni B areas. We present one case of plexiform schwannoma. A case of 24-year-old man with a one-year history of pain and swelling of the chest wall. Imaging showed a pleural-based mass with rib involvement which was excised and sent for histopathological evaluation. Diagnosis of plexiform schwannoma was confirmed by microscopic examination.These cases underscore the importance of recognizing plexiform schwannoma as a rare, but distinct entity, and differentiating it from other nerve sheath tumors with malignant potential. However, careful histopathological and immunohistochemical evaluation is very important for appropriate diagnosis and management of the patient.